2013
DOI: 10.5539/ass.v9n2p154
|View full text |Cite
|
Sign up to set email alerts
|

Quest for Tax Education in Non-Accounting Curriculum: A Malaysian Study

Abstract: This study aims (i) to ascertain the demand for tax education among Malaysian undergraduates from non-accounting disciplines; (ii) to examine the level of tax knowledge among non-accounting undergraduates; (iii) to identify the instructional methods to be used; and (iv) to determine the relevant tax topics to be covered in tax course for the non-accounting curriculum. A questionnaire was given to undergraduates from non-accounting disciplines in three public universities in Malaysia from the month of February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 14 publications
2
13
1
3
Order By: Relevance
“…As this study found that only 23.7% of respondents has high level of tax knowledge, the result suggests more emphasis on the importance of tax education especially in keeping to the newly implemented self-assessment system in Malaysia. The first large scale study on tax education in Malaysia was performed by several researchers as it involves three main public universities in Malaysia [22]. Questionnaire were distributed to 1,575 students in nonaccounting discipline and the results, supports previous studies, where a majority of the respondents are willing to take tax course as an elective paper.…”
Section: Literature Review 21 Tax Compliance and Tax Education Reseasupporting
confidence: 65%
See 4 more Smart Citations
“…As this study found that only 23.7% of respondents has high level of tax knowledge, the result suggests more emphasis on the importance of tax education especially in keeping to the newly implemented self-assessment system in Malaysia. The first large scale study on tax education in Malaysia was performed by several researchers as it involves three main public universities in Malaysia [22]. Questionnaire were distributed to 1,575 students in nonaccounting discipline and the results, supports previous studies, where a majority of the respondents are willing to take tax course as an elective paper.…”
Section: Literature Review 21 Tax Compliance and Tax Education Reseasupporting
confidence: 65%
“…The responses show that the main source of additional tax education, was gained from respondents' own reading (35 responses), 34 of them claimed that they received taxation education during their studies at tertiary level and 12 of them improved their knowledge through the IRBM collaboration programs with their workplace. Even though tertiary level education managed to provide additional tax knowledge as suggest by previous studies [4], [21], [22] it is only offered in programs with majors in Accounting and Business/Finance Programs [6] Therefore this finding provides further support for non-accounting programs at the tertiary level to offer taxation as their core subject. Collaboration programs between participants' workplace and the IRBM have also been reported as an important source of tax education after school.…”
Section: Section IV -Level Of Tax Knowledge Perception Towards Intromentioning
confidence: 64%
See 3 more Smart Citations